Transient protein-protein interactions: structural, functional, and network properties - Perkins, James Richard; Diboun, Ilhem; Dessailly, Benoit H; Lees, Jonathan G; Orengo, Christine A. (Elsevier, 2010)
Transient interactions, which involve protein interactions that are formed and broken easily, are important in many aspects of cellular function. Here we describe structural and functional properties of transient interactions between globular domains and between globular domains, short peptides, and disordered regions. The importance of posttranslational modifications in transient interactions is also considered. We review techniques used in the detection of the different types of transient protein-protein interactions. We also look at the role of transient interactions within protein-protein interaction networks and consider their contribution to different aspects of these networks.
Keywords: Interacciones proteína-proteína; Binding Sites; Computational Biology / methods; Protein Interaction Domains and Motifs*; Protein Interaction Mapping / methods*; Protein Binding